Tree mortality and bark-beetle abundance and species richness - Kärvemo, Simon; Björkman, Christer; Johansson, Therese; Weslien, Jan; Hjältén, Joakim (Dryad Digital Repository, 2017)
All data were collected in the field, tree mortality from transects (400 m/site) and bark beetle abundance and species richness from window traps. Sites=our names of the sites, RT90_X/Y=coordinates from RT90-projection, Treat=Treatments (G=gap-cuts, B=Burnes, C=Control), Sp.rich2010=Bark beetle (bb) species richness pre restoration, Abund2010=bb abundance pre restoration, Sp.rich_11_12=Two year bb species richness post restoration, Abund_11_12=Two year bb abundance post restoration, Sp.rich_11=First year bb species richness post restoration, Sp.rich_12=Second year bb species richness post restoration, Abund_pbb_11=First year primary bb abundance post restoration, Abund_pbb_12=Second year primary bb abundance post restoration, Abund_sbb_11=First year secondary bb abundance post restoration, Abund_sbb_12=Second year secondary bb abundance post restoration,